A mathematical model to predict the different isodose volumes using TRAK value in HDR intracavitary brachytherapy for revised Manchester and ICRU-89 based Point A plans using computer tomography images - Mourya A.; Choudhary S.; Sharma N.; Shahi U.P.; Singh G.; Pradhan S.; Aggarwal L.M. (My University, 2025)
Purpose: To find out the simple relationship between Total Reference Air Kerma (TRAK) and various isodose volumes. Calculated isodose volumes were compared with experimental data for revised Manchester and International Commission on Radiation Units and measurements (ICRU)-89 Point A-based treatment plans. The accuracy of the formula was compared with the results of other relationships available in the literature. Materials and Methods: Dosimetric data from 62 intracavitary brachytherapy (ICBT) treatment plans of 31 patients with cervical cancer were studied. Each patient had treatment plans normalized to revised Manchester and ICRU-89 Points A (A flange and A icru89). For each treatment plan, TRAK values, V 350, V 700, V 1050, and V 1400 were obtained. The modeling curve was plotted between Isodose volume (V d) and the ratio of d/TRAK obtained from A flange plans to get a mathematical relation. The results of this formula were compared with the experimental data and outcomes of other formulas available in the literature. A paired-sample t-Test was performed to assess the statistical significance. Results: In the case of revised Manchester-based A flange normalization plans, the mean isodose volume of V 350, V 700, V 1050, and V 1400 were 285.98 ± 32.3 cm 3, 101.96 ± 10.63 cm 3, 52.71 ± 4.72 cm 3, and 31.44 ± 2.33 cm 3 respectively. Likewise, for ICRU-89 based A icru89 normalization plans, the mean isodose volumes of V 350, V 700, V 1050, and V 1400 were 304.11 ± 26.17 cm 3, 108.88 ± 8.29 cm 3, 56.62 ± 3.69 cm 3 and 34 ± 2.23 cm 3 respectively. The mean difference was significant. The Mathematical relationship developed was [INLINE:1]. No correlation was found between TRAK and D 0.1cm 3,D 2cm 3 for organs at risk. Conclusions: The developed formula calculated isodose volumes within the accuracy of ± 3% in ICBT plans. © 2022 Wolters Kluwer Medknow Publications. All rights reserved.